Mapping child growth failure across low- and middle-income countries - Local Burden of Disease Child Growth Failure Collaborators (Nature, 2022)
This article was published in The Nature [ Copyright © 2020, The Author(s)] and the definite version is available at: https://doi.org/10.1038/s41586-019-1878-8 The Journal's website is at: https://www.nature.com/articles/s41586-019-1878-8